Qualidade de vida do paciente oncológico: contribuições das estratégias de enfrentamento e da inteligência emocional - Pereira, Fillipe Rodrigues Santos (Universidade Federal de São Carlos, 2025)
The psychosocial impact of cancer on quality of life makes it crucial to understand the role of resources such as coping strategies and emotional intelligence. This study investigates the interaction mechanism between these constructs. The aim was to refine the Escala de Estratégias de Enfrentamento para Pacientes Oncológicos and examine a model in which coping mediates the relationship between emotional intelligence and quality of life. A first psychometric study (N = 791), using exploratory structural equation modeling, found evidence of validity for a 12-item version of the scale (χ² (42) = 114.50, p < .001; CFI = .95; TLI = .92; RMSEA = .052 (90% CI [.039, .066]); SRMR = .036). A second study (N = 56) applied the Escala de Estratégias de Enfrentamento para Pacientes Oncológicos, the Questionário On-line de Regulação Emocional, and the Quality of Life Questionnaire Core, analyzing the data through regression and mediation analyses. The mediation analysis was the central finding, demonstrating a significant indirect effect: emotional regulation influenced quality of life exclusively through its positive impact on coping strategies (R² = .30). This finding elucidates a processual mechanism, indicating that emotional regulation is a distal resource that enables coping (a proximal resource). Therefore, interventions should focus on applying emotional skills to coping behaviors to effectively improve patients' quality of life.
Quality of life of cancer patients: contributions of coping strategies and emotional intelligence
Keywords: Enfrentamento; Inteligência emocional; Qualidade de vida; Psicometria; Neoplasias; Coping; Emotional intelligence; Quality of life; Psychometrics; Neoplasms; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA; 3. Saúde e Bem-Estar